Finite element analyses in geotechnical engineering - Part 3: An indispensable tool or a Mysterious Black Box? - Ong, Dominic E. L., Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/